2017
DOI: 10.1111/jvh.12818
|View full text |Cite
|
Sign up to set email alerts
|

Changes and analysis of anti‐HBs titres after primary immunization in 1‐ to 16‐year‐old Chinese children: A hospital‐based study

Abstract: Immunization with the hepatitis B vaccine is the most effective measure to prevent Hepatitis B Virus (HBV) infection. The aim of this study was to investigate the change in antibody levels induced by administration of the hepatitis B vaccine in children aged 1-16 year old in a large sample sized investigation. HBV markers were determined in 93 326 1- to 16-year-old hospitalized children who completed primary immunization as infants from south-west China, Chongqing. Analyses were performed on anti-HBs titre cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…The present study shows that the protective level of HBV antibody gradually decreasing with increase of age (Figure 4). Several studies conducted in different countries for example from Bangladesh [7], South Korea [18], Yemen [19], China [20], Ghana [17] and Palestine [21] observed the similar results. Now the question is, whether the booster vaccination is needed or not.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The present study shows that the protective level of HBV antibody gradually decreasing with increase of age (Figure 4). Several studies conducted in different countries for example from Bangladesh [7], South Korea [18], Yemen [19], China [20], Ghana [17] and Palestine [21] observed the similar results. Now the question is, whether the booster vaccination is needed or not.…”
Section: Discussionmentioning
confidence: 56%
“…Yue et al from China recommended that, for partial responders, a booster dose should be given. Without seroconversion or absence of any antibody, revaccination should be considered [20].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that those with a prebooster anti‐HBs level of ≤ 1 mlU/mL were less likely to mount an adequate anamnestic immune response (AIR) compared with those with a prebooster level of > 1 mlU/mL, which indirectly implies the significance and power of primary vaccination status in AIR induction. Furthermore, Yue et al demonstrated that the percentage of seroprotected individuals decreased and then increased with increasing age in the 1‐ to 16‐year‐old (YA) age groups, with the highest rate observed in the 1‐YA group of children who completed primary vaccination . The reason for the increasing rate in the 9‐16‐YA age groups was revaccination.…”
Section: Discussionmentioning
confidence: 99%
“…These results recommended for at-risk youths who had primary immunization to receive HepB booster. Our previous study has identi ed protective antibody (anti-HBs) in children declined with age, from 93.7% in 1-year-old to 42.3% in 9-year-old [13,14]. Whether there is protective immune response in children without anti-HBs is little known, and the need for booster doses is in debate.…”
Section: Introductionmentioning
confidence: 99%